The complete book of beauty - Helena Sunnydale (London Hermes House, 2010)
Offers psychological advice as well as information about skin care and health to help you make sound choices and increase self-confidence. This book features low-cost 'quick fixes' and easy-to-do tricks ranging from enhancing your mood to relieving puffy eyes. It also debunks myths about beauty, mental health, and cosmetic surgery.
Include Illustration, Glossary and Index.
The Complete Formula for Looking and Feeling Beautiful.
Keywords: Skin--Care and hygiene -- Beauty, Personal -- Cosmetics -- Women--Health and hygiene